Penyelesaian Wanprestasi dalam Pelaksanaan Perjanjian Jual Beli Sepeda Motor melalui Sistem Inden - Ainun Sabrina; Diah Aju Wisnuwardhani; Sunarjo Sunarjo; Fadilla Dwi Lailawaty (Bhirawa Law Journal, 2023)
Buying and selling can be done in various ways, one of which is a sale and purchase agreement with an indent system, namely buying an item by ordering and paying a down payment in advance. The legal issues that will be analyzed in this study are several acts of default that occurred at the Honda Ahass KartikaSari Pasar Besar Malang, both committed by the seller and the buyer in a motorcycle sale and purchase agreement through an indent system. Like; delays in the arrival of motorbikes, damage to motorbikes, and unilateral cancellation of orders by buyers. This study uses an empirical juridical method with a case approach and a statutory approach. The results of this study state that if within the time limit the motor pivot ordered by the seller has not arrived, then the down payment will be returned in full, if there is initial damage to the motorbike, it will be replaced with new spare parts in the damaged part of the motorbike and if the buyer suddenly canceling purchases through the pivot system before the specified time period, the buyer is subject to a fine of Rp. 800,000.